Penetrating xenophobic remoteness in interreligious encounters: Toward a pastoral praxis of befriending neighbouring in ‘pavement caregiving’ and ‘streetwise compassion’ - Daniël J. Louw (In die Skriflig, 2022)
Meeting the foreign and strange other should be viewed as a natural and inevitable feature of everyday life. When the other is endangering one’s comfort sones, especially in cases of ‘bread-and-butter’ questions, xenophobic fear sets in. Furthermore, when resistance is fuelled by fanatic expressions of religious self-maintenance or racial polarisation, xenophobic remoteness contributes to modes of discriminating suspicion, resistance of the strange other, even violent behaviour and forms of schismatic enmity. The concept of ‘befriending neighbouring’, based on the notion of compassionate being-with, could contribute to informal forms of friendship, the cornerstone for establishing ‘social coherence’. Thus, the question: How can convictions regarding the spiritual meaning of life and the content of religious belief systems, inspire faithful people to build bridges to one another within the normal circumstances of life? This article is a critical reflection on some of the basic presuppositions in some of the main religions and other philosophies of life, concerning the notion of compassion in caring for the strange other and the establishing of a more humane approach to the dynamics of everyday life.